Pengembangan Metode Suggestopedia Dalam Pembelajaran Mahârah Al-Kalâm Tingkat Menengah - Hurin In (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
This research is one way to overcome students' problems in decreasing abilities and motivation caused by boring learning situations, and also experiencing burnout in learning. Suggestopedia method is a suggestology, which states that humans can be directed to do something with suggestions and make efforts so that the mental capacity of human deposits that are still hidden can be mobilized for learning purposes by organizing a comprehensive system. In the suggestopedia method, the intermediate level of maharah al kalam learning is an oral review section called the oral review section, presenting new and discussed material, and also meditation. This study uses a library research type reaserch (library research), with a descriptive qualitative approach. Secondary data is data collected from information in the form of articles, electronic journals, and previous relevant theses and theses that have a relationship with the title of the research to be studied. From the results of the analysis the researcher found learning that was very fun, which was very satisfying and very ideal, soft chairs, soft light, and music were always available to add to the relaxed atmosphere. Posters (replaced every week) are installed displaying grammatical information on the target language with the intention of being able to benefit students in learning with the Suggestopedia Method. The materials for the suggestopedia method in Maharah al-Kalam, including: a) Memorization of vocabulary and symbols with the underlying grammar rules. b) The use of realistic (real) conversations and comments about the conversation. c) The use of pictures, dramatic stories, short stories, recitations, songs, and field trips where students can speak the target language. d) The use of phonetic transcription for vocabulary, introducing verb forms as early as possible, and the use of a tape recorder.